2021
DOI: 10.3390/ijms22031499
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin as a Functional Biomaterial for Tissue Engineering

Abstract: Tissue engineering (TE) is the approach to combine cells with scaffold materials and appropriate growth factors to regenerate or replace damaged or degenerated tissue or organs. The scaffold material as a template for tissue formation plays the most important role in TE. Among scaffold materials, silk fibroin (SF), a natural protein with outstanding mechanical properties, biodegradability, biocompatibility, and bioresorbability has attracted significant attention for TE applications. SF is commonly dissolved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
212
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(234 citation statements)
references
References 240 publications
1
212
0
Order By: Relevance
“…Silk fibers have been traditionally utilized as sutures in surgery for centuries. Recently, regenerated silk materials have been explored for possible applications in biomedicine [1]. A lot of studies indicated the cell attachment and proliferation on silk fibroin materials [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silk fibers have been traditionally utilized as sutures in surgery for centuries. Recently, regenerated silk materials have been explored for possible applications in biomedicine [1]. A lot of studies indicated the cell attachment and proliferation on silk fibroin materials [2].…”
Section: Resultsmentioning
confidence: 99%
“…Silk is a unique material, which has historically been regarded as high-grade raw materials of textile for its strength and luster. Recently, silk has become a promising biomaterial for tissue engineering because of several desirable properties [1]. In particular, these properties include biocompatibility, biodegradation, excellent mechanical properties, and versatility in processing into multiple materials formats [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many biopolymers and two-dimensional nanomaterials have shown great potential to increase their mechanical properties for future rough tissue engineering applications such as bone, cartilage, ligaments, and tendons. Upon using tissue scaffolds for skin and wound regeneration, the risk of scar tissue was demonstrated in some biopolymers such as silk fibroin [ 155 ]; thus, more research needs to be done to move towards safe clinical trials and approved products without any side effects based on these excellent biomaterials. Regeneration of rough tissues has other challenges, such as the kind of mineral content in bone tissue scaffold, which has an optimum in osteogenesis and an effect of the content on bone repair [ 156 ].…”
Section: Challenges and Future Prospects In Tissue Engineering Applicationsmentioning
confidence: 99%
“…(b) The scaffold should support host remodeling while retaining sufficient mechanical strength, inducing minimal inflammatory and immune responses, and avoiding disease transmission 8 . Currently, materials used for ligament/tendon scaffold construction include silk, 9 collagen, 10 polyglycolic acid (PGA), polylactic acid (PLA), 11 and PGA/PLA mixtures 12‐15 . Most of these materials do not share many characteristics with ligament/tendon ECM and fail to meet the standards for ideal scaffold construction.…”
Section: Introductionmentioning
confidence: 99%